THE CONFLICT BETWEEN WEIS TIMELENDERS COMPANY AND SOCIETY IN ANDREW NICCOL`S IN TIME - SIMANGUNSONG, HERWIN HALASAN (LANTERN (Journal on English Language, Culture and Literature), 2016)
This final project is entitled “The Conflict Between The Weis Timelenders Bank and Society in Andrew Niccol`sIn Time.” The aim of this final project is to describe the conflict in In Time`s. This final project adopts Marxist theory of capitalism. The theory is used to figure out the impact of capitalism on the society. The method used in this study is cinematic analysis and textual analysis. To get the data, the writer reads books and took some notes that are related to the topic, both trough the library research and the internet. The conclusion of this final project shows that the working class makes resistances to the capitalist; and the working class needs a freedom to actualize themselves.